LYMPHOCYTE-TO PLATELET ADHERENCE IN PATIENTS WITH ERYSIPELAS - A. N. Emelyanova; Yu. A. Vitkovskiy (Медицинская иммунология, 2014)
We observed twenty patients (12 women and 8 men) with erythematous-bullous erysipelas of moderate grade, and twenty patients (10 men and 10 women) with erythematous form of the disease, 45 to 55 years old. All the patients were diagnosed with primary inflammatory disease located at the lower extremities. The patients were admitted to the hospital within 1 or 3 days from the onset of clinical signs of the disease. In all patients, laboratory studies were performed at 3 and 12 days after clinical onset of the disease. Control group consisted of 55 age- and sex-matched healthy persons. All the patients received standard therapy, including antibiotics, desensitization and detoxifying drugs. Indices of l;ymphocyte-to-platelet adhesion (LPA) were determined in patients with different forms of erysipelas,. It has been found that LPA parameters were sharply decreased since the beginning of the disease, in spite of near-normal absolute lymphocyte counts, as compared with healthy controls at these terms. A simultaneous reduction in adherence was registered. At day 12, the LPA parameters were increased in the patients, with absence of significant changes in absolute lymphocyte contents against control values, the adhesion rates proved to be increased as well.  Hence, a reduced ability of blood lymphocytes to adhere to the surface of platelets was revealed in erysipelas. Dynamics of LPA parameters may serve as an indicator of treatment efficiency.